A Prospective Comparative Study of Sensorineural Hearing Loss in Patients with Head and Neck Cancers Treated with 2D RT vs. 3D CRT - Kumar, Prem; Khandelwa, Mayur; Kumar, H S; Sharma, Neeti; Lal Jakhar, Shankar (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Sensorineural hearing loss (SNHL) is a disabling condition for patients due to its chronic and often progressive nature. While conductive hearing loss (often observed after radiotherapy) is primarily reversible, SNHL is irreversible. Material and methods: This prospective randomized study was conducted in the Department of Radiation Oncology at S.P. Medical College in Bikaner, Rajasthan, India. The study was conducted from November 2020 to October 2021. After obtaining informed consent, 50 patients with biopsy-proven squamous cell carcinoma of the head and neck region were randomly assigned to two groups: Group A (receiving 2D RT at 2 Gy/fraction for 30 to 35 fractions over 6 to 7 weeks) and Group B (receiving 3D CRT at 2 Gy/fraction for 30 to 35 fractions over 6 to 7 weeks). Results: SNHL assessment was performed at the completion of treatment and 3 months later. At the completion of treatment, SNHL for speech frequencies was 15% in Group A (2D RT) and 8% in Group B (3D CRT), while high-frequency hearing loss was 45% and 28%, respectively. At 3 months post-treatment, SNHL for speech frequencies was 27.5% in Group A and 12% in Group B, and high-frequency hearing loss was 62.5% and 32%, respectively. Conclusion: High-frequency hearing loss can significantly impact quality of life by affecting speech discrimination. Conventional radiotherapy (2D RT) resulted in greater hearing loss compared to 3D conformal radiotherapy (3D CRT).